VERIFICATION OF THE SCIENTIFIC COMPONENT OF THE ACCOUNTING OF BUDGET INSTITUTIONS - BARDASH, Serhii; SHAPOVALOVA, Valentina; PASHKOVA, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the conditions of waging a war of liberation, the issues of financing defense capabilities and ensuring the fulfillment of social functions of the state are extremely complicated. For this reason, the primary task is to achieve the most effective management of public finances, a significant part of which is the financial assistance of the governments of the democratic countries of the world and international financial organizations. External financial assistance can be slowed down and reduced if it is not used effectively. The authorities of Ukraine faced the issue of ensuring the effectiveness of the management of state finances, which are a component of public finances, as well as the management of financial aid from donor countries and organizations, the solution of which is impossible without an accounting system adequate to the information requirements of the public sector. The purpose of the article is to determine the level of development of the accounting system, as a component of the field of scientific knowledge about accounting, formed by the scientific community of Ukraine. The research was conducted thanks to the use of critical analysis of scientific and other publications of Ukrainian researchers; a dialectical approach to the assessment of the development of scientific knowledge about accounting in the public sector; comparative analysis of the general development of accounting science and forecasting of its development prospects. It was established that accounting in the public sector is subject to unconditional influence, and therefore unconditional transformation to international standards. All scientific research is devoted to solving the problem of inefficient organization of accounting in the public sector. It was determined that the deep transformation of accounting in the public sector is possible under the condition of deepening scientific research and finding measures to improve accounting in the public sector both at the level of scientific knowledge and deepening its theory. Prospects for further research are systematic research and complex solution of accounting practice problems in the logical chain "practice - science - theory - practice".
Keywords: public sector; public sector accounting; budgetary institution; accounting of budgetary institutions; theory of accounting; system of scientific knowledge about accounting